2014
DOI: 10.1128/iai.01508-14
|View full text |Cite
|
Sign up to set email alerts
|

The δ Subunit of RNA Polymerase Guides Promoter Selectivity and Virulence in Staphylococcus aureus

Abstract: In Gram-positive bacteria, and particularly the Firmicutes, the DNA-dependent RNA polymerase (RNAP) complex contains an additional subunit, termed the ␦ factor, or RpoE. This enigmatic protein has been studied for more than 30 years for various organisms, but its function is still not well understood. In this study, we investigated its role in the major human pathogen Staphylococcus aureus. We showed conservation of important structural regions of RpoE in S. aureus and other species and demonstrated binding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…Analysis of RNA-seq data from the USA300 Houston strain demonstrate that the ctpA 2 gene is monocistronic and therefore can be disrupted without causing polar effects on downstream genes (Fig. S2) (Weiss et al, 2014). The mutant generated did not exhibit a growth defect under any laboratory growth conditions tested (data not shown).…”
Section: Analysis Of Ctpa Gene Expressionmentioning
confidence: 99%
“…Analysis of RNA-seq data from the USA300 Houston strain demonstrate that the ctpA 2 gene is monocistronic and therefore can be disrupted without causing polar effects on downstream genes (Fig. S2) (Weiss et al, 2014). The mutant generated did not exhibit a growth defect under any laboratory growth conditions tested (data not shown).…”
Section: Analysis Of Ctpa Gene Expressionmentioning
confidence: 99%
“…Since our RNAP composition studies showed that rpoZ deletion also results in ␦ depletion from RNAP, we next assessed whether removal of ␦ from the transcription complex was the driving force behind the observed changes. This is particularly important, as our previous studies have shown that ␦ is a key factor for maintaining transcriptional specificity within the S. aureus cell (8). Upon comparing RNA sequencing-derived transcriptional changes of the rpoE and rpoZ mutants, we found an overlapping regulon of only 24 genes (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Deletion of these subunits does not result in lethality for the cell, and thus their diminutive size and nonessential nature have resulted in their being classified as the "small accessory subunits" (reviewed in reference 6). Nevertheless, for the ␦ factor it has been shown that, in various species, deletion is accompanied by a deregulation of the transcriptional process, leading to decreased fitness and impaired virulence in pathogenic organisms (7,8). While there is an extensive history of research for ␦, has only recently been described as an RNAP subunit, with only a single study thus far performed in Bacillus subtilis (5), which suggested a role in phage immunity.…”
mentioning
confidence: 99%
“…This was explained by ␦-mediated changes in the requirement of iNTP by RNAP to stabilize the open complex formation at the promoters where the stability of the open complex formation is rate-limiting for transcription. Transcriptome analysis of S. aureus strains with and without ␦ show that the protein is not only involved in up-regulation of certain genes but is also involved in down-regulation of the genes that encode virulence factors (13).…”
mentioning
confidence: 99%